Eco-Innovative Solutions for Wasted Landscapes - Rigillo, Marina; Amenta, Libera; Attademo, Anna; Boccia, Lorenzo; Formato, Enrico; Russo, Michelangelo (Ri-Vista. Research for landscape architecture, 2018)
The paper focuses on the impact generated by the un-ement of wast on both natural environment, and urbanization process, and on the opportunity to invert it by regenerating Wasted Landscapes, i.e. underused, polluted and abandoned sites, especially lo-cated in peri-urban areas. This is one of the aims of the REPAiR project, funded in 2016 by the European Commission within the Horizon 2020 framework, developed by University of Na-ples with TU Delft as Lead Partner. The implementation of multi-scaling/multi-disciplinary ap-proach, for testing out collaborative decision-making, has seen so far the research of a scien-ea in the context of the Metropolitan Area of Naples. The selection of the peri-urban areas has also been tested through Living Labs, aimed at designing eco-innovative solutions towards circularity.